(untitled) (Journal of Universal Excellence, 2026)
Research Question (RQ): What is the level of education/training about lean production? Purpose: To conduct an empirical research based on the introduction of lean production, the level of knowledge and expertise in regards to the method and the general opinion about the introduction of lean production amongst the participants in the survey. Method: Based on a sample of 342 employees in chosen company we have conducted a quantitative research about the expertise and the introduction of the principals of lean production. Results: The key conclusion from the empirical part of the research is that more hours of education/training means a better knowledge of both the terminology of lean production and the purpose of a lean company. Organization: We have designed propositions for the improvement of the current level of expertise and the introduction of the principals of lean production. Society: Findings from this research will have theoretical and practical implications for all who try to introduce the principals of lean production in the future. Originality: Original research on employees’ education/training in lean manufacturing in the Republic of Slovenia. Limitations/Future Research: The survey was conducted in one manufacturing company, so the results will not be generalizable to other companies and other economic activity.